Induction of tumour necrosis factor (TNF) receptor type p55 and p75 in patients with chronic hepatitis C virus (HCV) infection - Kallinowski, Birgit; Rossol-Haseroth, Karin; Marinos, George; Hanck, C.; Stremmel, Wolfgang; Theilmann, Lorenz; Singer, Manfred V.; Rossol, Siegbert (Clinical & experimental immunology, 1998)
There is evidence that TNF-α contributes to the pathogenesis of chronic viral hepatitis. The cellular effects of this cytokine are regulated by two specific receptors, and membranous shedding of these receptors reflects activation of the TNF system. We performed a study of TNF-α and functionally active soluble TNF-receptors (TNFR-p55 and -p75) in 105 patients with chronic HCV infection. In HCV RNA-positive patients a significant enhancement of TNF-α and both receptor types was observed compared with controls (TNF-α 83.8 ± 91.7 pg/ml versus 18.8 ± 8.4 pg/ml, P < 0.001; TNFR-p55 1.4 ± 0.4 ng/ml versus 0.9 ± 0.2 ng/ml, P < 0.0001; TNFR-p75 6.4 ± 2.4 ng/ml versus 2.9 ± 0.6 ng/ml, P < 0.0001, respectively). The enhanced serum levels of TNF-α and TNFRs were reflected by a significant expression of TNFR-specific mRNA in peripheral mononuclear cells of HCV-infected patients (P < 0.001). Serum aminotransferases correlated with soluble TNFR-p75 (P < 0.001) but not with TNFR-p55 and TNF-α. We demonstrated an association of the degree of histological inflammation with both TNFRs (P < 0.01). Furthermore, enhanced hepatocellular expression of TNF-α and TNFRs could be demonstrated by immunohistochemical staining in HCV-infected patients. Sixty-eight out of 105 patients were treated with interferon-alpha (IFN-α) (3 × 106 U × 3/week). Pretreatment levels of TNF-α and TNFRs did not differ between responders and non-responders. Our results demonstrate that TNF-α and TNFRs are enhanced in chronic HCV infection and reflect histological activity of the disease. This up-regulation of TNFRs might modify host response and potentially contribute to liver damage in chronic HCV infection.
Gesehen am 24.06.2021